Beetroot (Beta vulgaris L.) reduces cholesterol and triglyceride in dyslipidemic male rats sprague–dawley model - Rohman, Yulia; Nurudhin, Arief; Wardhani, Lusi Oka (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2024)
Background: High-fat diets habit can lead to metabolic disorders, such as dyslipidemia which a significant contributor for cardiovascular diseases. Dyslipidemia occurs as a result of metabolically interrelated abnormalities of plasma lipids and lipoproteins, including low level of high-density lipoprotein cholesterol, and increasing of low density lipoprotein cholesterol, total cholesterol, and triglyceride. In order to enhance anti-lipid treatment, nutritional therapy containing bioactive compounds are investigated extensively, including those found in beetroot which shown potential in preventing and treating metabolic disorders.Objective: This study evaluated the effect of beetroot extract and beetroot juice on cholesterol and triglyceride levels as a dyslipidemia treatment, in comparison to simvastatin. Ethanol extract can attract flavonoids and betalain, but the extraction process can degrade fiber. Meanwhile, juice still contains quite a lot of fiber.Materials and Methods: Male Sprague Dawley rats were divided into seven groups and fed different diets for 56 days. The groups were: normal control (K0), negative control-HFD (KN), positive control-HFD + simvastatin (KP), single-dose treatment with BE (P1) or BJ (P2), and combination treatment with BE or BJ + simvastatin (P3 and P4), each intervention was given for 28 days. After blood drawn, cholesterol total and triglyceride serum were examined and analyzed.Results: Administration of beetroot extract and juice in single dose or combination with simvastatin gave a significant decrease in cholesterol and triglyceride levels compared to before the intervention. The average reduction levels of cholesterol in P1, P2, P3, and P4 were 54.81, 56.31, 94.19 and 69.11 respectively. Whereas the average decreasing level of triglyceride were 43.28, 30.78, 54.28 and 46.37 in P1, P2, P3 and P4 groups. Combination treatment with simvastatin gave more reduction level compared with single dose beetroot extract or beetroot juice. The most effective reduction was in the beet extract combination with simvastatin group were -94.19±4.08 mg/dL (cholesterol) and -54.28±6.93 mg/dL (triglyceride).Conclusion: Both beetroot extract and juice, as single or combined with simvastatin, were able to decrease cholesterol and triglyceride levels, these indicated their potential for prevention and therapeutic in dyslipidemia. Further research is needed to investigate its mechanisms and establish optimal dosages for human consumption.